Accuracy of Patient-Specific 3D Printed Drill Guides in the Placement of a Canine Coxofemoral Toggle Pin through a Minimally Invasive Approach - Darrow, Brett G.; Snowdon, Kyle A.; Hespel, Adrien (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this study was to evaluate the accuracy of patient-specific three-dimensional printed drill guides (3D-PDG) for the placement of a coxofemoral toggle via a minimally invasive approach.Materials and Methods Pre-procedure computed tomography (CT) data of 19 canine cadaveric hips were used to design a cadaver-specific 3D-PDG that conformed to the proximal femur. Femoral and acetabular bone tunnels were drilled through the 3D-PDG, and a coxofemoral toggle pin was placed. The accuracy of tunnel placement was evaluated with post-procedure CT and gross dissection.Results Coxofemoral toggle pins were successfully placed in all dogs. Mean exit point translation at the fovea capitis was 2.5 mm (0.2–7.5) when comparing pre- and post-procedure CT scans. Gross dissection revealed the bone tunnel exited the fovea capitis inside (3/19), partially inside (12/19) and outside of (4/19) the ligament of the head of the femur. Placement of the bone tunnel through the acetabulum was inside (16/19), partially inside (1/19) and outside (2/19) of the acetabular fossa. Small 1 to 2 mm articular cartilage fragments were noted in 10 of 19 specimens.Clinical Significance Three-dimensional printed drill guide designed for coxofemoral toggle pin application is feasible. Errors are attributed to surgical execution and identification of the borders of the fovea capitis on CT data. Future studies should investigate modifications to 3D-PDG design and methods. Three-dimensional printed drill guide for coxofemoral toggle pin placement warrants consideration for use in select clinical cases of traumatic coxofemoral luxation.
Keywords: coxofemoral luxation; toggle pin; dog; three-dimensional printed drill guide; minimally invasive